ABOUT GREAT NUMBER OF VALUES OF SIZES OF DEFECTS FOR WHOLE ONE CURVE OF SCINCHENNOGO ORDER - Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It is shown, that great number of values of sizes of defects for the arbitrary whole curve of finished order no more than calculated although the great number not of collinear between itself imperfect vectors for such crooked can have power continuum.